Drug Release from Inert Spherical Matrix Systems Using Monte Carlo Simulations - Villalobos, Rafael; V. Garcia, Erika; Quintanar, David; M. Young, Paul (Current Drug Delivery, 2017)
Background: Computational approaches for predicting release properties from matrix devices have recently been purposed as an approach to better understand and predict such systems. The objective of this research is to study the behavior of drug delivery from inert spherical matrix systems of different size by means of computer simulation. Methods: To simulate the matrix medium, a simple cubic lattice was used, which was sectioned to make a spherical macroscopic system. The sites within the system were randomly occupied by drug-particles or excipient-particles in accordance with chosen drug/excipient ratios. Then, the drug was released from the matrix system simulating a diffusion process. Results: When the released fraction was processed until 90% release, the Weibull equation suitably expressed the release profiles. On the basis of the analysis of release equations, it was found that close to the percolation threshold an anomalous released occurs, while in the systems with an initial drug load greater than 0.45, the released was Fickian type. It was also possible to determine the amount of drug trapped in the matrix, which was found to be a function of the initial drug load. The relationship between the two mentioned variables was adequately described by a model that involves the error function. Based on the these results and by means of a non-linear regression to the previous model, it was possible to determine the drug percolation threshold in these matrix devices. Conclusion: It was found that the percolation threshold is consistent with the value predicted by the percolation theory.
Keywords: spherical matrix systems